Determination of individual diffusion coefficients of alkane solvent(s)–CO2–heavy oil systems with consideration of natural convection induced by swelling effect. (April 2017) - Shi, Yu; Zheng, Sixu; Yang, Daoyong
Highlights: Determination of individual diffusion coefficient with considering natural convection. Diffusion tests of solvent(s)–CO2 –heavy oil systems under elevated temperatures. Diffusion coefficients larger than those obtained with conventional methods. Achievement of a higher mass transfer rate with the aid of elevated temperature. Natural convection has flow direction opposite to that of gas-heavy oil mass transfer. Abstract: By both coupling heat and mass transfer and characterizing heavy oil as multiple pseudocomponents, a new and pragmatic technique has been developed to determine individual diffusion coefficient of each component in alkane solvent(s)–CO2 –heavy oil mixtures with consideration of natural convection induced by swelling effect. Experimentally, diffusion tests of alkane solvent(s)–CO2 –heavy oil systems are conducted with a visualized PVT cell under elevated temperatures and a constant pressure. Theoretically, the Peng-Robinson equation of state, heat transfer equation, and diffusion-convection equation are coupled to form a mathematical matrix where diffusion coefficient and viscosity of the mixture are considered to be concentration-dependent. Diffusion coefficients of each component of a gas mixture in liquid phase are respectively determined once either the deviation between the experimentally measured and theoretically calculated mole fraction of CO2 and/or solvent(s) or the deviation between the experimentally measured dynamic swelling factors and the theoretically calculated ones has been minimized. Also, effects of heat and natural convection on the mass transfer of CO2 and/or solvent(s) in heavy oil have been examined. The individual diffusion coefficient of each component in a mixture is found to be larger than those documented in the literature, while thermal equilibrium is able to achieve much faster than mass transfer for the entire system. A higher temperature is beneficial to enhance the mass transfer rate in a certain range, while natural convection induced by swelling effect results in a fluid flow direction opposite to that of the mass transfer, and thus decreasing the mass transfer rate under the same conditions.